Jorge Kajuru total: modos de presença de uma vedete midiática - Yassuda, Maria Adélia Ziolli (2007)
This study investigates the construction in the ways of presence of Jorge Kajuru in his performance as presenter of a sports reporter for television. Our corpus was delimited in last the two months of propagation of the program Esporte Total, under the command of Jorge Kajuru, period that understands the months of April and May of 2004, and still integrates the corpus others media texts randomly select. The problematic of the object was based in the Semiotics developed around Algirdas Julien Greimas, in special, his narrative grammar and the discursive level, of which the figurative and enunciative mechanisms are explored. Jorge Kajuru obtains to assume in the variation of his performance a transitory existence semiotics between the categories that one that is included and that one that is including. He explores a universe cultural of subjects and figures of the sphere of the privacy from which he serves himself to give sustentation the interactive relation with the interested Brazilian viewer in the sports, more necessarily, in the soccer, thematic central office of its program. In his approach, Jorge Kajuru creates links between situations that the ethics of the daily one in general propagate in his Esporte Total and, from which infers the scienter of the presenter for the establishment of an adhesion contract that creates effect of sensible of secular concurrence in relation to the moment of reception of the program. Our hypothesis is that Jorge Kajuru constructs himself with a way of being himself from the rearrangement of the paper of narrator in first person, assuming himself in the majority of the times as interlocutor who dialogues directly, as if in a body the body with the interlocutee. In this case, the hearing, that is installed in interlocution act to produce effect of uncurling of a colloquy of abetters between Kajuru and the viewer, who divides of the same ethical values and social behavior. The figure of the presenter can be taken as well as the one of a subject that if constructs as declared and emerges in the articulation with a "individuated identity" by means of the considered effect of interaction in the ways as it says what he says